Fluorinated molecular diamond improved polymer electrolytes enable stable cycling with high capacity of all-solid-state lithium-metal batteries - Mengbing Zhuang; Yuan Liao; Junshuai Liang; Yixiao Deng; Jin-Cheng Zheng; Hao Yan; Tinglu Song; Yang Dai (Journal of Materiomics)
The interfacial incompatibility of the poly (ethylene oxide)-based electrolytes hinder the longevity and further practice of all-solid-state batteries. Herein, we present a productive additive 1-Fluoroadamantane facilitating to the distinct performance of the poly (ethylene oxide)-based electrolytes. Attributed to the strong molecular interaction, the coordination of the Li+-EO is reduced and the ‘bonding effect’ of anion is improved. Thus, the Li + conductivity is promoted and the electrochemical window is widened. The diamond building block C10H15− strengthens the stability of the solid polymer electrolytes. Importantly, the 1-Fluoroadamantane mediates the generation of LiF in the interfaces, which fosters the interfacial stability, contributing to the long-term cycling. Hence, the symmetric cell (Li/Li) exhibits a long-term lithium plating/stripping for over 2,400 h. The 4.3 V LiNi0.8Mn0.1Co0.1O2/Li all-solid-state battery with the 1-Fluoroadamantane-poly (ethylene oxide) improved electrolyte delivers 600 times, with an impressive capacity retention of 84%. Also, the cell presents high capacity of 210 mA·h/g, and 170 mA·h/g at 0.1 C and 0.3 C respectively, rivalling the liquid electrolytes.